2017
DOI: 10.1098/rstb.2016.0258
|View full text |Cite
|
Sign up to set email alerts
|

The dialectic of Hebb and homeostasis

Abstract: One contribution of 16 to a discussion meeting issue 'Integrating Hebbian and homeostatic plasticity'. It has become widely accepted that homeostatic and Hebbian plasticity mechanisms work hand in glove to refine neural circuit function. Nonetheless, our understanding of how these fundamentally distinct forms of plasticity compliment (and under some circumstances interfere with) each other remains rudimentary. Here, I describe some of the recent progress of the field, as well as some of the deep puzzles that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
222
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(236 citation statements)
references
References 60 publications
(102 reference statements)
1
222
1
Order By: Relevance
“…Many studies have confirmed this original result in vitro [6], as well as ex vivo in acute slices prepared from both juvenile and adult animals that had previously undergone in vivo deprivation [7][8][9][10][11][12][13][14]. Synaptic scaling does have layer-specific properties in cortex, where scaling in layer 4 is limited to early development [7], but layer 5 [12,15] and layer 2/3 [10] can scale throughout adulthood.…”
Section: Mechanisms Of Homeostatic Stabilizationmentioning
confidence: 71%
See 2 more Smart Citations
“…Many studies have confirmed this original result in vitro [6], as well as ex vivo in acute slices prepared from both juvenile and adult animals that had previously undergone in vivo deprivation [7][8][9][10][11][12][13][14]. Synaptic scaling does have layer-specific properties in cortex, where scaling in layer 4 is limited to early development [7], but layer 5 [12,15] and layer 2/3 [10] can scale throughout adulthood.…”
Section: Mechanisms Of Homeostatic Stabilizationmentioning
confidence: 71%
“…Changing the activity of inhibitory neurons provides an important homeostatic mechanism by which activity levels can be rapidly (within seconds) adjusted through the increase or the decrease in the firing rate of inhibitory neurons to prevent short-term increases in activity levels that would be associated with pathological activity such as seizures; however, recent work suggests that minimizing changes to inhibition helps maintain temporal coding in the network, which is shaped by the inhibitory circuit [37], so some maintenance of inhibitory tone is likely essential for the circuit. Adjusting synaptic strength or neuronal excitability occurs over much longer time courses of hours [6], which would be much too slow to account for activity peaks that would potentially cause pathological over-excitation.…”
Section: Mechanisms Of Homeostatic Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several lines of theoretical and experimental evidence, spanning several synaptic and intrinsic components as candidate mechanisms, for concurrent emergence of encoding, stability and activity homeostasis. These lines of evidence also argue for significant advantages when encoding, homeostasis and stability mechanisms are concurrent (Anirudhan and Narayanan, 2015;Honnuraiah and Narayanan, 2013;Ibata et al, 2008;Johnston and Narayanan, 2008;Johnston, 2007, 2010;Nelson and Turrigiano, 2008;Triesch, 2007;Turrigiano, 2011;Turrigiano, 2008Turrigiano, , 2017Zenke et al, 2017).…”
Section: Degeneracy In Metaplasticity and In Maintaining Stability Ofmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/203943 doi: bioRxiv preprint first posted online Oct. 16, 2017;Turrigiano, 1999Turrigiano, , 2008Turrigiano, , 2017Turrigiano and Nelson, 2000;van Rossum et al, 2000;Zenke et al, 2017). A prominent theme that spans several such stability theories is metaplasticity (Abraham, 2008;Abraham and Bear, 1996;Abraham and Tate, 1997;Hulme et al, 2013), where the profile of plasticity concomitantly changes with the induction of plasticity (Fig.…”
Section: Degeneracy In Metaplasticity and In Maintaining Stability Ofmentioning
confidence: 99%